Las fronteras de la Ilustración: itinerarios entre Historia y Derecho - Demarchi, Giacomo (Historia del Derecho, 2021)
Thanks to the specialist's contributions with different backgrounds and trajectories, this volume attempts to encourage a few forays into the frontiers of Enlightenment assumptions. These assumptions have managed to cement in the projects raised by Western legal culture over the last three centuries. With a diachronic and transatlantic perspective, the contributors confront the dynamics where the border became a perimeter and a limit. Border conceives capable of stabilising and absorbing society's structural tensions, only to open up or break, when the illusion of having reached the perfect building collided with the discovery of structural cracks. Hence, at this time, it rised a reflection on the foundations that had made the will and the individual the inexcusable (which does not mean exclusive) elements of the decline of the political and legal aspects of the Western culture. In the second half of the 20th century, this 'West' came to make man-citizen and his rights the parameters of the humanity, reaching the frontier where the reflection and praxis of power are still moving today.